Characterization and expression of two avirulence genes cloned from Pseudomonas syringae pv. glycinea. - Tamaki, S (1988)
Two avirulence genes, avrB and avrC, from race 0 of Pseudomonas syringae pv. glycinea, were sequenced and found to encode single protein products of 36 and 39 kilodaltons, respectively. The proteins had neither recognizable signal peptide sequences nor significant stretches of hydrophobic amino acids that might indicate membrane association. Both avrB and avrC had relatively low position 3 and overall G+C contents, which suggests that they may have been recently introduced into P. syringae pv. glycinea. The deduced amino acid sequences of the proteins encoded by avrB and avrC shared 42% identical amino acids. However, when introduced into race 4 of P. syringae pv. glycinea, each gene directed a unique pattern of hypersensitive reactions on several differential soybean cultivars. The avrC protein was overproduced in Escherichia coli cells and deposited as insoluble inclusion bodies in the cell cytoplasm. The avrC protein could be solubilized with urea-octyl glucoside treatment, but neither the solubilized protein nor the intact inclusion bodies elicited a hypersensitive reaction in soybean leaves.